Perlindungan Hak Asasi Manusia Pada Penanganan Kasus Kekerasan bagi Perempuan dan Anak di Indonesia - Alya, Dian (CV WAHANA PUBLIKASI, 2023)
One of the most complex and important issues in the context of human rights protection in Indonesia is the Criminal Acts of Violence Against Women and Children. Questions about the effectiveness of human rights protection in the Indonesian legal system arise as a result of cases of violence experienced by parents and children. This study aims to analyze how human rights are used in prosecuting various cases of violence against children that are often experienced by adults and children in Indonesia. The method used is normative empirical research with a case approach and decision-making rules. To identify sources of law and fraud within the framework of international standards for human rights in Indonesia, the collected data were analyzed qualitatively. Although Indonesia has adequate legal provisions to protect human rights, their implementation is often inconsistent, especially in cases involving individuals and children, according to the results of the study. Human rights protection is not optimal in cases of violence against women and children due to accountability and structural barriers.